Thesaurus-2 or about the thesaurus approach again - Lamazhaa, Chimiza K. (The New Research of Tuva, 2013)
Review to: Lukov Val.A., Lukov Vl.A. Thesaurus-2: thesaurus approach to understanding the human and its world. M.: National Institute of business Publishing House, 2013 – 640 p.
Keywords: review; the thesaurus approach; edition-2013; Moscow University for the Humanities